DESCRIPTION OF TNI SOLDIERS’ KNOWLEDGE OF DISASTER VICTIM’S EVACUATION AND TRANSPORTATION IN BATALYON ARHANUD 13/PBY - An Nisa Ul-Misbah (Jurnal Keperawatan Malang, 2021)
The TNI executes other military operations than war, namely helping to cope with natural disasters (evacuation and transportation), shelter, and providing humanitarian assistance. The TNI’s knowledge in this action is paramount concern because the TNI is included in the rescue team when a disaster occurs. The purpose of this research is to know the knowledge of TNI soldiers about the evacuation and transportation of disaster victims. The research instrument used a questionnaire about the evacuation and transportation of disaster victims. This research used quantitative research with descriptive research design and non-random sampling approach (purposive sampling) to 127 soldiers. Data analysis was conducted by using frequency distribution. Characteristic data processing showed that the average age of the respondents was 25.06 years old, the highest rank was the Prada rank of 56 soldiers (44.1%), the most letting was in 2018 with 23 soldiers (18.1%). The results of the research on the knowledge of TNI soldiers about evacuation and transportation were in the poor category, namely 84 soldiers (66.1%). The researcher hopes the TNI will conduct training on the evacuation and transportation of disaster victims to soldiers.